The Efforts of the Pekanbaru Mayor in Addressing and Managing the Issue of Foreign Refugees in Pekanbaru City - Febmahduni, Mahartika; Rinaldi, Kasmanto (Jurnal Ilmiah Teunuleh, 2025)
Pekanbaru City has become one of the destinations for foreign refugees, particularly those from conflict-affected countries such as the Rohingya, Afghanistan, and Pakistan. The increasing number of refugees has led to various challenges, especially in social and security aspects, necessitating serious attention and management from the local government. This study aims to examine the efforts undertaken by the Mayor of Pekanbaru in addressing the presence of foreign refugees within the city. The research employs a descriptive qualitative approach, with data collection techniques including interviews with the National Unity and Political Agency (Badan Kesatuan Bangsa dan Politik), community leaders, local residents, as well as document analysis and relevant secondary data. The findings indicate that the implemented measures include both penal and non-penal approaches. The penal approach is applied to minor violations through placement in the Immigration Detention Center (Rumah Detensi Imigrasi/Rudenim), while handling serious violations is hindered by language barriers and the unclear citizenship status of the refugees. Meanwhile, the non-penal approach involves establishing a Foreign Refugee Handling Task Force (Satgas Penanganan Pengungsi Luar Negeri/PPLN), conducting public awareness campaigns and education, and planning refugee relocations in collaboration with the UNHCR and IOM. These policies reflect the city government’s efforts to balance law enforcement and humanitarian protection for foreign refugees in Pekanbaru.